Intelligent Decision Support System for Higher Education Helpdesk - Norhaira, Nordin (2006)
Education is the responsibility of the Federal Government and Malaysia is committed to providing sound education to all. The Vision 2020 is to make Malaysia, a centre of educational excellence at international level. To achieve that mission, we need to continuously improve the standard of higher education so as to produce quality graduates that would meet the needs of the nation for skilled workforced human resource. There is over 1000 degree programs offered by several universities in Malaysia every year. Each program has different qualification rules and condition that an applicant needs to consider before applying for places at higher institutions in Malaysia. In some cases, applicant will face lots of problem such as to make a correct decision and get the proper advice within limited period of time. One way to overcome this problem is by providing information and advisory service online. In conjunction with that, an Intelligent Decision Support for Higher Education Help-Desk is designed/ developed to assist student to identify their potential in some program offered in public and private university based on their qualification. A decision support system (DSS) can take many different forms and generally, DSS is a computerized system for helping make decisions. The proposed system uses Case-Based Reasoning (CBR) technique has been employed to assist users, in decision making. The studies also include identifying suitable CBR design for intelligent decision support for helpdesk. A new with specified attributes or know as CBR attributes is presented to the system, the engine then computes the similarity value will give the best recommendation on degree program to assist student to undertake. The system has been tested with real case data and the result shows that CBR engine is able to recommend a suitable program for various users.